Regions of acquired uniparental disomy at diagnosis of follicular lymphoma are associated with both overall survival and risk of transformation - O'Shea, Derville (American Society of Hematology, 2009)
Acquired homozygosity in the form of segmental acquired uniparental disomy (aUPD) has been described in follicular lymphoma (FL) and is usually due to mitotic recombination. SNP array analysis was performed with the use of the Affymetrix 10K 2.0 Gene-chip array on DNA from 185 diagnostic FL patients to assess the prognostic relevance of aUPD. Genetic abnormalities were detected in 118 (65%) of 182 patients. Number of abnormalities was predictive of outcome; more than 3 abnormalities was associated with inferior overall survival (OS; P < .03). Sites of recurrent aUPD were detected on 6p (n = 25), 16p (n = 22), 12q (n = 17), 1p36 (n = 14), 10q (n = 8), and 6q (n = 8). On multivariate analysis aUPD on 1p36 correlated with shorter OS (P = .05). aUPD on 16p was predictive of transformation (P = .03) and correlated with poorer progression-free survival (P = .02). aUPD is frequent at diagnosis of FL and affects probability of disease transformation and clinical outcome.